A Mn-doped CoP / CoO@NF material and its preparation method and application

The preparation of Mn-doped CoP/CoO@NF materials through two-step hydrothermal method and one-step phosphating method has solved the problems of complex catalyst preparation and insufficient performance in the prior art, and achieved efficient electrochemical hydrogen evolution and urea electrooxidation, improving the The stability and functional diversity of the catalyst are achieved.

CN118441310BActive Publication Date: 2025-01-17SICHUAN AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410545545.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-01-17
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

The preparation process of existing electrocatalytic hydrogen evolution catalysts is cumbersome and difficult to be used for large-scale production. The synergistic effect between CoP and MXene is limited, resulting in insufficient catalytic performance, only HER catalytic activity, and single function.

Method used

The Mn-doped CoP/CoO@NF material was prepared by two-step hydrothermal method and one-step phosphating method. Secondary hydrothermal doping was performed through KMnO4, and the phosphorus source usage was regulated to obtain the best CoP and CoO ratio and increase the charge. Transfer ability and active sites to achieve bifunctional catalytic activity of HER and UOR.

Benefits of technology

The catalyst preparation process is simplified, the catalytic activity and stability are improved, and the electro-oxidation performance of electrochemical hydrogen and urea is achieved, with reduced overpotential and excellent electrochemical stability, which is suitable for overall water decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118441310B_ABST
    Figure CN118441310B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a Mn-doped CoP / CoO@NF material and a preparation method and application thereof, wherein the material is specifically Mn‑CoP / CoO@NF, and the present invention adopts a method of two hydrothermal processes and one phosphating process, which can be mass-produced, and the process is simple and easy to operate. In view of the shortcomings of insufficient catalytic active sites and single catalytic activity of the catalyst prepared in the above technical scheme, the present invention adopts a method of regulating the degree of phosphating, obtaining the optimal ratio of CoP and CoO content, so as to enhance charge transfer, and utilizing a method of doping Mn with secondary hydrothermal processes, thereby inducing the generation of more active sites and improving the catalytic activity, so that the material has the dual-functional catalytic activity of HER and UOR (electrocatalytic urea oxidation), and can be used for overall water decomposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a Mn-doped CoP / CoO@NF material and a preparation method and application thereof. Background Art

[0002] The limited traditional fossil energy, greenhouse gas emissions and the requirements of industrial development have led to an increasing global demand for green renewable energy. However, renewable energy such as wind, solar and tidal energy is characterized by discontinuity and volatility. Hydrogen (H2) is a high-quality energy with high energy density and no carbon emissions during use. Using non-periodic renewable energy to electrocatalytically split water to produce hydrogen is an effective way to produce hydrogen, which can promote the utilization and promotion of new energy. However, the large-scale commercial use of hydrogen production by electrolysis of water is limited by the high price of precious metal catalysts and the high energy consumption caused by the slow kinetics of overall water decomposition. In an acidic environment, the hydrogen evolution reaction HER is easy to occur, but due to the poor stability of the catalyst in an acidic environment, alkaline hydrogen evolution is more widely studied at present. In the catalytic process, the OER process of four-electron transfer plays an important role in the overall reaction rate, but the OER process usually has a large overpotential. Therefore, on the whole, developing non-precious metal-based catalysts with lower hydrogen evolution overpotential under alkaline conditions and using the easier urea molecular electrooxidation reaction (UOR) instead of the OER process are effective improvement measures. On the one hand, they can achieve efficient hydrogen evolution, and on the other hand, they can also deal with urea pollution.

[0003] Among non-precious metal-based catalysts, transition metal phosphides (TMPs) (such as CoP, NiP, and FeP) with wide sources, low prices, and high catalytic activity have great application potential. The introduction of P atoms can change the D band center (average energy of d electrons) and Fermi level of the metal, resulting in changes in catalytic activity. The negatively charged P sites of TMPs can act as Lewis bases to capture positively charged protons, which may make the Gibbs free energy of H (Had) adsorbed by TMPs close to zero, achieving efficient hydrogen evolution. At the same time, the active oxyhydroxyls (such as CoOOH, NiOOH, and FeOOH) formed by the surface reaction of TMPs can serve as actual active sites to promote the OER or UOR reaction. Among TMPs, CoP has attracted widespread attention in the field of electrocatalysis due to its advantages such as high catalytic activity, good conductivity, good thermal stability, and good alkali resistance. However, the catalytic activity of pure CoP is always limited. Doping CoP with metal elements can further improve its electrocatalytic performance. Chinese patent document CN116791140A discloses a synthesis strategy for Mn-doped CoP / MXene heterostructure catalysts used for hydrogen production by electrolysis of water. It uses divalent cobalt salts such as cobalt nitrate and manganese chloride, manganese salts, and two-dimensional MXene as raw materials. With the assistance of organic solvents such as urea and polyvinyl pyrrolidone, Mn-doped CoP / MXene materials are prepared through a series of steps such as ultrasound, reflux, freeze drying, annealing, and phosphating, showing relatively good hydrogen evolution (HER) performance. However, the preparation process of this material is cumbersome and difficult to use for large-scale production. In addition, the synergistic effect between CoP and MXene is limited, and the active sites induced by the mixed doping Mn are insufficient. Therefore, the catalytic performance of this material for HER is limited, and it currently only shows HER catalytic activity, and its function is relatively single.

[0004] The present invention uses a simple two-step hydrothermal method and a one-step phosphating method to prepare Mn-doped CoP / CoO@NF materials, and uses KMnO4 for secondary hydrothermal to achieve Mn doping, which can expose more active sites and promote surface reconstruction. And by regulating the amount of phosphorus source used, a material with an optimal ratio of CoP and CoO can be synthesized to improve the charge transfer ability. The Mn-doped CoP / CoO@NF material finally obtained can have excellent hydrogen evolution performance and urea electro-oxidation performance at the same time.

[0005] The existing Chinese patent document CN202310788441.1 discloses the preparation method and application of hydrogen evolution electrocatalytic composite materials. A divalent cobalt salt and a divalent manganese salt are mixed with a first organic solvent to form a solution A; urea and polyvinyl pyrrolidone are mixed with a second organic solvent to form a solution B; a two-dimensional MXene is mixed with water to form a solution C; the solution A, solution B, and solution C are mixed under an inert gas atmosphere, ultrasonically treated, and then refluxed, and then washed and freeze-dried to obtain Mn-Co Pre / MXene powder; the Mn-Co Pre / MXene powder is subjected to high-temperature annealing treatment under an inert gas atmosphere to obtain Mn-CoO / MXene powder; the Mn-CoO / MXene powder is subjected to high-temperature phosphating treatment under the condition of the participation of a phosphorus source under an inert gas atmosphere to obtain the Mn-doped CoP / MXene heterostructure composite material. The Mn-doped CoP / MXene heterostructure composite material can be used as a water electrolysis catalyst for electrocatalytic hydrogen evolution reaction.

[0006] However, the above invention has the following defects: the preparation process of the material is cumbersome and difficult to use for large-scale production. In addition, the synergistic effect between CoP and MXene is limited, and the active sites induced by the mixed doping of Mn are insufficient, so the catalytic performance of the material for HER is limited (current density is 10 mA / cm 2 The corresponding overpotential is 95 mV). At present, it only exhibits HER catalytic activity and has a relatively single function. Summary of the invention

[0007] The purpose of the present invention is to provide a Mn-doped CoP / CoO@NF material and a preparation method and application thereof. The present invention adopts a method of two hydrothermal processes and one phosphating process, which can be mass-produced, and the process is simple and easy to operate. In view of the shortcomings of insufficient catalytic active sites and single catalytic activity of the catalyst prepared in the above technical scheme, the present invention adopts a method of regulating the degree of phosphating to obtain the optimal ratio of CoP and CoO content to enhance charge transfer, and uses a method of doping Mn by secondary hydrothermal process to induce more active sites and improve the catalytic activity, so that the material has the dual-functional catalytic activity of HER and UOR (electrocatalytic urea oxidation), and can be used for overall water decomposition.

[0008] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0009] A Mn-doped CoP / CoO@NF material, specifically Mn-CoP / CoO@NF, an in-situ synthesized Mn-doped CoP / CoO@NF catalyst on a nickel foam (NF) substrate, for achieving efficient electrochemical hydrogen evolution (HER), urea electro-oxidation (UOR) and overall urea-assisted water splitting.

[0010] On the other hand, the present invention provides a method for preparing the above-mentioned Mn-doped CoP / CoO@NF material, comprising the following steps:

[0011] S1: Dissolve a certain amount of Co(NO3)2·6H2O, urea and NH4F in 30 mL of deionized water;

[0012] S2: Transfer the above solution into a 50 mL reactor and then add the pretreated nickel foam;

[0013] S3: Place in a forced air drying oven and keep at 100 °C for 8 h;

[0014] S4: After the insulation is completed and cooled to room temperature, the nickel foam is taken out and washed three times with deionized water and ethanol respectively to obtain Co-pre@NF;

[0015] S5: Prepare a KMnO4 solution with a certain molar concentration using KMnO4 and deionized water;

[0016] S6: Take 30 mL of the solution prepared in step S5 and transfer it to a 50 mL reactor, then add Co-pre@NF;

[0017] S7: Place in a forced air drying oven and keep at 180 °C for 1 h to obtain CoMn-pre@NF;

[0018] S8: The obtained CoMn-pre@NF and 0.1-0.9g of phosphorus source NaH2PO2·H2O were placed in a tube furnace, with CoMn-pre@NF placed downstream and phosphorus source placed upstream. Under the protection of inert gas, the temperature was raised to 300°C at a heating rate of 2°C per minute and kept for 2 h for phosphating treatment, and finally Mn-doped CoP / CoO@NF was obtained.

[0019] Furthermore, in S1, the molar amounts of Co(NO3)2·6H2O, urea and NH4F are 2 mmol, 10 mmol and 8 mmol, respectively.

[0020] Furthermore, in S2, the size of the nickel foam is 2 cm×4 cm, and the pretreatment method is: ultrasonic in 2M HCl, acetone, deionized water and ethanol for 30 min, respectively, and then dried at 60 °C in a vacuum drying oven for 6 h. After cooling to room temperature, the pretreated nickel foam can be obtained, which is used as a substrate material for the in-situ growth of the catalyst and can also improve the conductivity of the catalyst.

[0021] Further, in S5, 2.5 mmol KMnO4 was fully dissolved in 100 mL deionized water to obtain a 25 mM KMnO4 solution.

[0022] Furthermore, in S8, the amount of NaH2PO2·H2O phosphorus source used is 0.5 g.

[0023] On the other hand, the present invention proposes the application of the above-mentioned materials and preparation methods in overall urea-assisted water splitting.

[0024] Beneficial effects of the present invention:

[0025] The structure of the Mn-doped two-dimensional nanosheets coated one-dimensional nanowire clusters obtained by the present invention has a high specific surface area and abundant active sites, wherein the one-dimensional nanowire clusters provide a direct channel for charge transfer, and the coated two-dimensional nanosheets can increase the electrochemical active surface area. This structural design optimizes the charge transfer and the diffusion dynamics of the reactants, so that each active site can effectively participate in the catalytic reaction. The advantage of this design is that it provides an intracellular heterogeneous structure, which can coordinately regulate the charge density and reaction field in the local environment, thereby improving the catalytic efficiency and selectivity.

[0026] During the synthesis process, the nickel foam substrate carries a large number of three-dimensional porous structures, which can directly serve as carriers to support the attachment and growth of catalytically active substances. The three-dimensional porous structure of the nickel foam is conducive to the infiltration of the electrolyte and improves the conductivity of the catalyst. The catalyst in the present invention is prepared by two hydrothermal processes and one-step phosphating, which is easy to operate and can be mass-produced. The hydrothermal method uses water as a reaction medium. Under the synergistic effect of heating and pressure, the catalytic precursor is transformed into a target catalytic material. The self-assembly phenomenon in this process helps to form a predetermined nanostructure. The phosphating step is carried out in a stable inert gas environment, which is conducive to controlling the phosphating reaction to achieve the optimal formation ratio of CoP and CoO. Specifically, the higher the amount of phosphorus source used, the higher the CoP content will be, while the CoO content will be reduced. By controlling the degree of phosphating, we can fine-tune the electronic properties and interactions of the catalyst surface, thereby adjusting its catalytic performance.

[0027] The surface charge recombination caused by Mn doping is one of the key factors to improve the electrocatalytic performance. The introduction of Mn elements can effectively regulate the electrochemical activity of transition metals by changing the d orbital electron distribution of CoP / CoO. The heterogeneous interface formed by CoP and CoO provides an excellent synergistic catalytic effect, in which CoP may be responsible for the efficient hydrogen evolution activity, while CoO provides the necessary oxidation active sites in the urea electrooxidation (UOR) reaction. The regulation of the ratio of CoP to CoO enhances the charge transfer. Mn doping leads to the redistribution of interfacial charge, regulates the electronic structure of the catalyst, promotes surface reconstruction during the catalytic process, and produces sites with higher catalytic activity, which promotes the catalytic reaction. This dual synergistic effect in structure and composition greatly improves the performance of the catalyst in HER and UOR reactions.

[0028] Overpotential is a basic indicator for measuring the catalytic activity of water electrolysis catalysts. That is, the smaller the overpotential, the less energy required for the reaction and the lower the energy consumption. The present invention adopts a simple method to prepare Mn-doped CoP / CoO@NF catalysts, which exhibit excellent hydrogen evolution activity and electrocatalytic urea oxidation activity: under a three-electrode system, in 1 M KOH electrolyte, 10 mA / cm 2 At a current density of 1.34 W, the overpotential of HER is only 66 mV; in an electrolyte of 1 M KOH and 0.33 M urea, 10 mA / cm 2 The UOR potential is only 1.318 V vs. RHE (reversible hydrogen electrode) at a current density of 50 mA / cm 2 At the current density, after continuous cycling for 24 hours, the catalytic activity did not decay significantly, showing excellent electrochemical stability. In addition, in order to simulate the actual application of electrolysis of urea, we used human urine containing 1 M KOH as the electrolyte. Under the two-electrode system, only a potential of 1.40 V was required to reach 10 mA / cm 2 The current density is 2.447 W, which shows the potential for purifying urea-rich wastewater.

[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 Scanning electron microscope (SEM) image of Mn-doped CoP / CoO;

[0032] Figure 2 High-resolution transmission electron microscopy (HRTEM) images of Mn-doped CoP / CoO;

[0033] Figure 3 X-ray photoelectron spectroscopy (XPS) of Mn-doped CoP / CoO;

[0034] Figure 4 X-ray diffraction pattern (XRD) of Mn-doped CoP / CoO;

[0035] Figure 5 HER linear sweep voltammetry (LSV) curves of Mn-doped CoP / CoO, CoP, MnO, NF, and PtC;

[0036] Figure 6 is the HER Tafel slope (Tafel) of Mn-doped CoP / CoO, CoP, MnO, NF, and PtC;

[0037] Figure 7 Mn doped CoP / CoO at 50 mA / cm 2 Chronovoltage curve (HER) at current density of ;

[0038] Figure 8 UOR linear sweep voltammetry (LSV) curves of Mn-doped CoP / CoO, CoP, MnO, and NF;

[0039] Fig. 9 is the UOR Tafel slope (Tafel) of Mn-doped CoP / CoO, CoP, MnO, and NF;

[0040] Fig.10 Mn doped CoP / CoO at 50 mA / cm 2 Chronovoltage curve at current density (UOR);

[0041] Fig.11 Linear sweep voltammetry curves of urea full electrolytic cell composed of RuO2||PtC, NF||NF, Mn-CoP / CoO||Mn-CoP / CoO;

[0042] Fig.12 The chronovoltage curve of Mn-CoP / CoO||Mn-CoP / CoO in 1 M KOH and 0.33 M urea as electrolyte;

[0043] Fig.13 The linear sweep voltammetric curve of Mn-CoP / CoO||Mn-CoP / CoO in a full electrolytic cell containing 1M KOH and human urine;

[0044] Fig.14 HER linear sweep voltammetric curves of different phosphorus source usage and unphosphorized materials;

[0045] Fig.15 is the HER Tafel slope of different phosphorus source usage and unphosphated materials;

[0046] Fig.16 The UOR linear sweep voltammetric curves of different phosphorus source usage and unphosphated materials;

[0047] Fig.17 is the UOR Tafel slope of the material with different phosphorus source usage and unphosphated material. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0049] The present embodiment describes a Mn-doped CoP / CoO@NF material, specifically Mn-CoP / CoO@NF, in which a Mn-doped CoP / CoO@NF catalyst is in situ synthesized on a nickel foam substrate (NF) to achieve efficient electrochemical hydrogen evolution (HER), urea electro-oxidation (UOR) and overall urea-assisted water splitting.

[0050] On the other hand, the present invention provides a method for preparing the above-mentioned Mn-doped CoP / CoO@NF material, comprising the following steps:

[0051] S1: Dissolve a certain amount of Co(NO3)2·6H2O, urea and NH4F in 30 mL of deionized water;

[0052] S2: Transfer the above solution into a 50 mL reactor and then add the pretreated nickel foam;

[0053] S3: Place in a forced air drying oven and keep at 100 °C for 8 h;

[0054] S4: After the insulation is completed and cooled to room temperature, the nickel foam is taken out and washed three times with deionized water and ethanol respectively to obtain Co-pre@NF;

[0055] S5: Prepare a KMnO4 solution with a certain molar concentration using KMnO4 and deionized water;

[0056] S6: Take 30 mL of the solution prepared in step S5 and transfer it to a 50 mL reactor, then add Co-pre@NF;

[0057] S7: Place in a forced air drying oven and keep at 180 °C for 1 h to obtain CoMn-pre@NF;

[0058] S8: The obtained CoMn-pre@NF and 0.1-0.9 g of phosphorus source NaH2PO2·H2O are placed in a tubular furnace, with CoMn-pre@NF placed downstream and phosphorus source placed upstream. Under the protection of inert gas, the phosphating treatment is carried out at a certain heating rate and a certain temperature, and finally Mn-doped CoP / CoO@NF is obtained.

[0059] In this embodiment, in S1, the molar amounts of Co(NO3)2·6H2O, urea and NH4F are 2 mmol, 10 mmol and 8 mmol, respectively.

[0060] In this embodiment, in S2, the size of the nickel foam is 2 cm×4 cm, and the pretreatment method is: ultrasonic in 2 M HCl, acetone, deionized water and ethanol for 30 min, then dried in a vacuum drying oven at 60 ° C for 6 h, and cooled to room temperature to obtain the pretreated nickel foam, which is used as a substrate material for the in-situ growth of the catalyst and can also improve the conductivity of the catalyst.

[0061] In this example, in S5, 2.5 mmol KMnO4 is fully dissolved in 100 mL deionized water to obtain a 25 mM KMnO4 solution.

[0062] In this embodiment, in S8, the optimal phosphorus source usage of NaH2PO2·H2O is 0.5 g.

[0063] On the other hand, the present invention proposes the application of the above-mentioned materials and preparation methods in overall urea-assisted water splitting. Example 2

[0064] As described in this example, the in-situ grown Co-pre@NF nanowires on nickel foam were prepared, including the following steps:

[0065] S1: The nickel foam (2 cm×4 cm) was ultrasonically cleaned with dilute hydrochloric acid (1M), acetone, deionized water and ethanol for 30 min respectively, dried in a vacuum oven at 60 °C for 12 h, and cooled to room temperature for later use;

[0066] S2: Weigh 2 mmol Co(NO3)2·6H2O, 10 mmol urea and 8 mmol NH4F, dissolve in 30 mL aqueous solution, and stir for 30 min to form a solution;

[0067] S3: Pour the above solution into a 50 mL reactor, then put the pretreated nickel foam (2 cm×4 cm) into the reactor, keep it at 100 °C for 8 h, cool it to room temperature, wash it with deionized water and ethanol three times respectively, and dry it in a forced air drying oven at 60 °C for 6 h to obtain Co-pre@NF. Example 3

[0068] As described in this embodiment, the CoMn-pre@NF nanomaterial grown in situ on nickel foam is prepared, including the following steps:

[0069] S1: Weigh 2.5 mmol KMnO4 and dissolve it in 100 mL deionized water. Stir for 30 min to form a solution.

[0070] S2: Pour 30 mL of the above solution into a 50 mL reactor, put the prepared Co-pre@NF (2 cm×4 cm) into the reactor, and then keep it at 180 °C for 1 h. After cooling to room temperature, wash it with deionized water and ethanol three times respectively, and dry it in a forced air drying oven at 60 °C for 6 h to obtain CoMn-pre@NF. Example 4

[0071] As described in this example, the in-situ Mn-doped CoP / CoO@NF grown on nickel foam was prepared, including the following steps:

[0072] S1: Weigh the most preferred 0.5 g NaH2PO2·H2O and put it into a porcelain boat, put CoMn-pre@NF into another porcelain boat, and wrap the whole boat with aluminum foil, and poke appropriate ventilation holes.

[0073] S2: Place the NaH2PO2·H2O side toward the upstream of the tube furnace and the CoMn-pre@NF toward the downstream. Heat to 300 ℃ at a heating rate of 2 ℃ / min in an Ar atmosphere and keep it warm for 2 h to allow the phosphine produced by the decomposition of NaH2PO2·H2O to react with the solid CoMn-pre@NF. After natural cooling, Mn-doped CoP / CoO@NF can be obtained. Example 5

[0074] Characterization and analysis of Mn-doped CoP / CoO@NF

[0075] like Figure 1SEM image of Mn-doped CoP / CoO. The two-dimensional nanosheets grown on the one-dimensional nanowire clusters have a high specific surface area and provide a large number of active sites.

[0076] like Figure 2 The (HR)TEM image of Mn-doped CoP / CoO is shown. HRTEM results show that the composite material is composed of two phases, CoO and CoP, where the interplanar spacing of 0.254 nm corresponds to the (111) crystal plane of CoO, and the interplanar spacing of 0.197 nm corresponds to the (112) crystal plane of CoP.

[0077] like Figure 3 The XPS graph of Mn-doped CoP / CoO is shown. The full XPS spectrum shows that the composite material contains Co, Mn, P, and O elements.

[0078] like Figure 4 The XRD pattern of Mn-doped CoP / CoO is shown. As can be seen from the figure, for CoP, the diffraction peaks of the three crystal planes (110), (111) and (211) can be clearly seen. For CoO, the diffraction peaks of the three crystal planes (111), (200) and (220) can be clearly seen, and no Mn peak is observed. Combined with the XPS full spectrum analysis, this is because Mn exists in an amorphous form.

[0079] like Figure 5 The HER linear sweep voltammetry (LSV) curves of Mn-doped CoP / CoO, CoP, MnO, NF, and PtC are shown in the figure. It can be seen from the figure that at 10 mA / cm 2 At a current density of , the overpotentials of Mn-doped CoP / CoO, CoP, MnO, NF, and PtC are 66 mV, 102 mV, 218 mV, 267 mV, and 27 mV, respectively, indicating that Mn-doped CoP / CoO has the hydrogen evolution performance closest to that of the precious metal PtC catalyst in 1 M KOH electrolyte.

[0080] like Figure 6 The Tafel slopes of Mn-doped CoP / CoO, CoP, MnO, NF, and PtC are shown in the figure. It can be seen from the figure that the potentials of Mn-doped CoP / CoO, CoP, MnO, NF, and PtC are: 40.42 mV dec -1 、58.21 mV dec -1 、122.25 mV dec -1 、128.22 mV dec -1 and 52.26 mV dec -1 , Mn-doped CoP / CoO has the best catalytic reaction kinetics in 1M KOH electrolyte.

[0081] like Figure 7 The stability test curve of Mn-doped CoP / CoO is shown in Figure 2. The chronopotentiometry was used at 50 mA / cm 2 At a current density of 2.5 Å, the activity of the catalyst showed almost no decay after 24 h of electrocatalysis, indicating that Mn-doped CoP / CoO has excellent HER electrochemical stability.

[0082] like Figure 8 The UOR linear sweep voltammetry (LSV) curves of Mn-doped CoP / CoO, CoP, MnO, and NF are shown in the figure. It can be seen from the figure that at 10 mA / cm 2 At the current density of , the potentials of Mn-doped CoP / CoO, CoP, MnO and NF are 1.318 V, 1.352 V, 1.361 V and 1.415 V, respectively. The potential of Mn-doped CoP / CoO is the smallest (1.318 V), indicating that Mn-doped CoP / CoO has the best urea electro-oxidation performance in the electrolyte of 1 M KOH and 0.33 M urea.

[0083] like Fig. 9 The Tafel slopes of Mn-doped CoP / CoO, CoP, MnO, and NF are shown in the figure. As can be seen from the figure, the Tafel slopes of Mn-doped CoP / CoO, CoP, MnO, and NF are: 58.48 mV dec -1 、102.77 mV dec -1 、74.95 mV dec -1 , and 158.07 mV dec -1 Among them, the Tafel slope of Mn-doped CoP / CoO is the smallest (58.48 mV dec -1 ), indicating that Mn-doped CoP / CoO has the fastest catalytic reaction kinetics in the electrolyte of 1 M KOH and 0.33 M urea.

[0084] like Fig.10 The stability test curve of Mn-doped CoP / CoO is shown in Figure 2. The chronopotentiometry was used at 50 mA / cm 2 At a current density of 2.34 W, the activity of the catalyst decayed slightly after 24 h of electrocatalytic urea oxidation, indicating that Mn-doped CoP / CoO has good electrochemical stability for UOR.

[0085] like Fig.11 The linear sweep voltammetric curves of RuO2||PtC, NF||NF, Mn-CoP / CoO||Mn-CoP / CoO composed of urea full electrolytic cell (electrolyte is a solution of 1 M KOH and 0.33 M urea) are shown at 50 mA / cm2 At a current density of 1.5, their potentials are 1.415, 1.476, and 1.7, respectively, indicating that Mn-CoP / CoO has the best performance when applied to overall water splitting.

[0086] like Fig.12 The stability of Mn-CoP / CoO||Mn-CoP / CoO was tested using an electrolyte containing 1 M KOH and 0.33 M urea. The chronopotentiometry was used at 50 mA / cm 2 After electrocatalytic urea oxidation at a current density of 36 h, the activity of the catalyst decayed very little, indicating that Mn-doped CoP / CoO has good overall electrochemical stability for water splitting in an electrolyte containing 1 M KOH and 0.33 M urea, and can achieve the goal of low-energy full electrolysis of urea to produce hydrogen.

[0087] like Fig.13 The linear sweep voltammetric curve of Mn-CoP / CoO||Mn-CoP / CoO in a full electrolytic cell containing 1M KOH and human urine is shown in Figure 1. 2 At a current density of 1.40 V, overall water decomposition can be achieved at a potential of only 1.40 V, showing good practicality.

[0088] like Fig.14 The HER linear sweep voltammetry (LSV) curves of different phosphorus source usage and unphosphorized materials are shown. It can be seen from the figure that at 10 mA / cm 2 At the current density of , the overpotentials of CoMn-pre, Mn-CoP / CoO 0.1, Mn-CoP / CoO 0.5, and Mn-CoP / CoO 0.9 are 215 mV, 79 mV, 66 mV, and 80 mV, respectively. Mn-CoP / CoO 0.5 has the best HER performance, indicating that 0.5 g is the optimal amount of phosphorus source used.

[0089] like Fig.15 The HER Tafel slopes of the materials without phosphating and different phosphorus source usage are shown. The potentials of CoMn-pre, Mn-CoP / CoO 0.1, Mn-CoP / CoO 0.5, and Mn-CoP / CoO 0.9 are: 99.77 mV dec -1 、46.18 mVdec -1 、40.42 mV dec -1 , and 42.18 mV dec -1 Among them, Mn-CoP / CoO 0.5 has the smallest potential (40.42 mVdec -1), indicating that Mn-CoP / CoO 0.5 has the fastest catalytic reaction kinetics, indicating that 0.5 g is the optimal amount of phosphorus source used.

[0090] like Fig.16 The UOR linear sweep voltammetry (LSV) curves of different phosphorus source usage and unphosphated materials are shown. It can be seen from the figure that at 10 mA / cm 2 At the current density of , the potentials of CoMn-pre, Mn-CoP / CoO 0.1, Mn-CoP / CoO 0.5 and Mn-CoP / CoO 0.9 were 1.356 V, 1.339 V, 1.318 V and 1.323 V, respectively. Mn-CoP / CoO 0.5 had the best UOR performance, indicating that 0.5 g was the optimal amount of phosphorus source used.

[0091] like Fig.17 The UOR Tafel slopes of the materials without phosphating and different phosphorus source usage are shown. The potentials of CoMn-pre, Mn-CoP / CoO 0.1, Mn-CoP / CoO 0.5, and Mn-CoP / CoO 0.9 are: 84.05 mV dec -1 、72.29 mVdec -1 、58.48 mV dec -1 , and 68.28 mV dec -1 Among them, Mn-CoP / CoO 0.5 has the smallest potential (58.48 mVdec -1 ), indicating that Mn-CoP / CoO 0.5 has the fastest catalytic reaction kinetics in the electrolyte of 1 M KOH and 0.33 M urea, indicating that 0.5 g is the optimal amount of phosphorus source used.

[0092] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a Mn-doped CoP / CoO@NF material, characterized in that: The material is specifically a Mn-CoP / CoO@NF catalyst doped with Mn synthesized in situ on a nickel foam substrate; The following steps are involved: S1: Dissolve a certain amount of Co(NO3)2·6H2O, urea and NH4F in 30 mL of deionized water; S2: Transfer the above solution into a 50 mL reactor and then add the pretreated nickel foam; S3: Place in a forced air drying oven and keep at 100 °C for 8 h; S4: After the insulation is completed and cooled to room temperature, the nickel foam is taken out and washed three times with deionized water and ethanol respectively to obtain Co-pre@NF; S5: Prepare a KMnO4 solution with a certain molar concentration using KMnO4 and deionized water; S6: Take 30 mL of the solution prepared in step S5 and transfer it to a 50 mL reactor, then add Co-pre@NF; S7: Place in a forced air drying oven and keep at 180 °C for 1 h to obtain CoMn-pre@NF; S8: The obtained CoMn-pre@NF and 0.1-0.9 g of phosphorus source NaH2PO2·H2O were placed in a tube furnace, with CoMn-pre@NF placed downstream and phosphorus source placed upstream; under the protection of inert gas, the temperature was increased to 300 °C at a rate of 2 °C per minute and kept at this temperature for 2 h for phosphating treatment, and finally Mn-doped CoP / CoO@NF was obtained; In S1, the molar amounts of Co(NO3)2·6H2O, urea, and NH4F are 2 mmol, 10 mmol, and 8 mmol, respectively; In S2, the size of the nickel foam is 2 cm×4 cm, and the pretreatment method is: ultrasonication in 2M HCl, acetone, deionized water and ethanol for 30 min, respectively, followed by drying at 60 °C in a vacuum drying oven for 6 h, and then cooling to room temperature to obtain the pretreated nickel foam.

2. The method for preparing the Mn-doped CoP / CoO@NF material according to claim 1, characterized in that: In S5, 2.5 mmol KMnO4 was fully dissolved in 100 mL deionized water to obtain a 25 mM KMnO4 solution.

3. The method for preparing the Mn-doped CoP / CoO@NF material according to claim 1, characterized in that: In S8, the amount of NaH2PO2·H2O phosphorus source used was 0.5 g.

4. Use of the Mn-doped CoP / CoO@NF material prepared by the method according to any one of claims 1 to 3 as an electrode in overall urea-assisted water splitting.

Citation Information

Patent Citations

  • Preparation method and application of Mn-doped CoP / MXene heterostructure composite material

    CN116791140A

  • Preparation of cobalt phosphide / cobalt manganese phosphide with hollow hierarchical structure and application of cobalt phosphide / cobalt manganese phosphide in electrolyzed water

    CN113955728A